RETORIKA DALAM RAGAM TUTUR TEMBANG PEMENTASAN DRAMA TARI ARJA (LPPM IKIP PGRI Bali, 2018)
Arja dance theatre is basically a music dance drama that uses vocal rhetoric of tembang with the title sourced from the banner story (malat). His melodic dramatic story with his ability to compose aspects of  speech, utilizing such a style of language aims to create a certain effect or power far the audience. So his functioning is dynamic, interesting, memorable and meaning ful. Lately the attention and the interest of balinese towards the arts of arja dance theater seems to be getting less fans. Balinese people recenly prefer to enjoy the instant entertainment that aired on TV. The audience is attention to the arts of arja is very diminished. It is cavsed by the amergence of arja cuddly or arja ?bondres?which the dancers are all men complete arja dance theatre is increasingly not getting the audience. But based on the observations of some researchers, there is still a group of complete arja can get the audience in their performance namely the? Kesenian Dramatari Arja RRI Denpasar?. This arja group still survive as a complete arja which has its own charm far the fans. It is because the plagers are very shrewd in using the style of speech song, it becomes a rhetorical learning and manners far the audience. As such, the study used a descriptive-qualitative design. Data colection was done through methods of observations and interviews,while techniques of data collection were done through a tape recording and note-taking. The data analysis was done in terms of theory on rhetoric.